Keberadaan Harimau Sumatera (Panthera Tigris Sumatrae) dan Satwa Mangsanya di Berbagai Tipe Habitat Pada Taman Nasional Tesso Nilo (The Existence of Sumatran tiger (Panthera tigrissumatrae) andanimal’s enemy in various types of Habitat at Tesso Nilo Natio - Riyan Sumitran; Defri Yoza; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Sumatran Tiger is the one and only tiger’s species which is still survive by Indonesia after Bali Harimau and Java Harimau which is have become extinct already.The conversion of Forest become other landsuch asHTI(Industrial Plantation Forest) andpalm oilplantationsattend effect ofconflictbetweenhumansandtigers. The dataof this studyis expected tobe areference forconflictmitigation. This observation used by using transectmethod in 5 m width. The observation observe toward the sign ofthe existence oftigersandtheir animalspeciesin form oftrail, dirt, scratches, the rest of theanimal. Every existence of the tiger there will be a vegetation analysis by making plot. The Result found that there is existence of tiger at 3 transect and 3 segment of secondary forest, 3 transect and 6 segment at HTI. Meanwhile, there is no founding of tiger existence at palm oil. The effect transforming of conversion becoming palm oil is there is no existence of the tiger itself, it because of the high of human’s activity. Key Words : Sumatera Tiger, animal enemy, sign of existence, the effect of conversion.